If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4r = 6r + -1 Reorder the terms: 4r = -1 + 6r Solving 4r = -1 + 6r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-6r' to each side of the equation. 4r + -6r = -1 + 6r + -6r Combine like terms: 4r + -6r = -2r -2r = -1 + 6r + -6r Combine like terms: 6r + -6r = 0 -2r = -1 + 0 -2r = -1 Divide each side by '-2'. r = 0.5 Simplifying r = 0.5
| 4+11d= | | 7-(4*4-10)+x=10 | | x^2-3xy+10=0 | | 8n^2+5-613=0 | | 2y+7=-9 | | 6r+2(4r-3)=8 | | 2y-9=2y+3 | | 14a=-8 | | x+1-2-(-2x+3)=x+5-(2-1) | | 7x^2-49x-14=0 | | 5x^2+2x=195 | | x+1-2-(-2x+3)=x+5-(2-1) | | 14b=-8 | | 9x-2y=-24 | | -3(x+10)=-22 | | 3m+45m=1.5 | | (3-5i)+(7-8i)=0 | | 2(x-1)+4x=34 | | 5x+20y=24 | | x-1-2-(-2x+3)=x+5-(2-1) | | -19=3x+5 | | 239-11k=41 | | 10x^4-7x^3+20x^2=0 | | 4x+5y=-20fory | | p(12+23)= | | N+(n+32)=126 | | 8a+3=11 | | 0.019s+s=15 | | 3(9x-30)=51 | | Y+4=-2y | | 9x+6=5x-26 | | 8xv=-21 |